Literacy intervention for preschool children at risk of literacy difficulties in Malaysia - Yeo, K. J. (Horizon Research Publishing, 2019)
The purpose of this study was to evaluate an early literacy intervention programme for preschool children who are at risk for literacy difficulties. This study was designed based on the ADDIE instructional design framework: Analysis of needs, Designing intervention program and test, Developing and validating intervention module, materials, and test, Intervention, and Evaluation of the effectiveness of the intervention. A total of 64 kindergarten children from 10 preschools who were native speakers of Malay children – 32 intervention and 32 control, participated in this experimental study. Pretest and posttest were administered using Malay Early Literacy Skills Test Battery (MELSTB). Paired samples t-tests indicated that both groups progressed significantly in phonological awareness, reading, spelling and reading comprehension skills. However, intervention group significantly outperformed the control group in all literacy skill posttests. This study offered a viable intervention alternative within preschool curriculum.